A vida é um filme, um sonho: a (des)razão de amar em Federico Fellini - Abreu, Eliane Maria de (2015)
This research has as the main objective establish connections between the theme of love, one of the most important aspects in the work of the psychiatrist Ludwig Binswanger, and the ways of being of the Italian filmmaker Federico Fellini's characters: Cabíria, in Le notti di Cabíria, Guido, in 8 e ½, and the musicians in Prova d'orchestra. The phenomenological-existential approach, which Binswanger is one of the greatest representatives, is used in this paper as general theoretical fitting. Along with the love matter, Fellini's characters analysis gradually made room for the unreason and dreams matters. As the characters's life stories are closely related to the clownery theme, the clown's way of being is omnipresent as organizing course of the analysis. The clown's vibration or way of being, in their correlation with the unreason and the world of dreams, was used as one of the main interpretation aspects, given the importance of clowns and the circus in the filmmaker's life and work. The development of this research was leaded by the following question: would love be a gag to Federico Fellini and his characters?